Studi Eksegesis Terhadap Kata ‘Tanpa Alasan’ (εἰκῇ ) Pada Kata ‘Marah’ Dalam Matius 5:22 Menurut Naskah Byzantium Dan Komparasinya Terhadap Novum Testamentum Graece (Nestle-Aland Edisi Ke-27) - Heny Heny (Kaluteros Jurnal Teologi Dan Pendidikan Agama Kristen, 2021)
Based on observations on the theological issues that occur at then current writer mendiskripsi is it some thing as background writing this work, including the following: first, the interpretation of the difference resulting from the use of the original language of the Bible is well seen from outside parties i.e. the view of the Islamic religion and views the Jewish religion, as well as from Parties within the IE view of Christianity itself, Second, more specifically the views of Islamic religious figures who say that the Bible is corrupted. K etiga, from among the Christian religion itself there is the memasalahkan process of translation and the translation of results from the original language texts are taken from the existing texts, translations and consider which one is superior (the original script approach) than others. For example there is one book called "The KJV (King James Version)-NIV (New International Version) the Debate" by Jeffrey Khoo of Far Eastern Bible College, Singapore. In addition, the Jehovah's witnesses also issued a statement that there is ' 50,000 errors in the Gospel ' from the magazine Awake (Awake) volume 38 No. 17 September 8, 1957, and much material delivered through another edition. And the program used by the Islamic religious figures, one of them Late. Ahmed Deedat in his book 'Is the Bible God's Word?' who use the resources of the Jehovah's witnesses in his book, even in other books as well. The writing of history sources: written sources. Written materials are usually the most important source for historians to reconstruct history. This resource is divided into two categories: (1) history written in passing or official, and (2) the history of written carefully according to the rules of writing of history (based on the library). History written in passing include the ' raw data ' of history, from the records produced by all levels of society, starting with an individual level to the international level. In doing research there are some which are used to examine cases that are in the books that will be examined. Because covered are comparing the two texts are actually related, so the methods that used a combination of several methods. Moreover, comparing the texts of Scripture, so keep in mind the previous method used, i.e. as follows: form criticism, Literary Criticism and critique texts. Criticism of the Bible can be divided into two parts; i.e. High Criticism and critique. This type of study could be applied to the Bible, because it is named after the biblical research. Christian Encyclopedia defines: "science to achieve a satisfactory knowledge of the origin, history, and circumstances of the original text of the Bible." I need to know the history of high criticism and criticism of low as well as its development, namely as follows: the term "criticism" always refers to a negative connotation. Though not always have to be so. The sense of the term principal criticism was the examination or testing of an issue, or a problem with the intention of determining the keotentikannya, the keterandalannya, or its significance. " Criticism of the term basically means an opinion, or an act of judgment; derived from the verb in the language of Greece (... [crino]) means of judging, or testing, or forward tudingan or charges against, or sets, a row of the meaning of the above meaning. If used in the fields of literature, he suggests thinking – not an attempt at finding errors – but with a fair and properly assess the goodness and evil things openly and objectively. In other words, is an impartial appraisal, or anything similar to that for example it anything that could be considered by certain critics. " Both methods above criticism in a high Criticism that is form criticism and criticism of literature. While the Text Criticism is Criticism.